The Use of Collaborative Strategic Reading (CSR) to Enhance the Students’ Reading Comprehension Achievement at Junior High School - Devita Puspita Sari; Siti Masrifatul Fitriyah; Zakiyah Tasnim (English Education Study Program, 2021)
This classroom action research aimed to enhance the eighth grade students’ reading comprehension achievement by using Collaborative Strategic Reading (CSR) and to know how CSR enhanced the students’ participation during learning process of reading comprehension. The research participants were the VIII A grade students of SMPN 1 Pakusari. The data were collected by using reading comprehension test and observation during the teaching and learning process of reading comprehension. After that, the data were analyzed using descriptive statistic to know the students’ reading comprehension achievement and their participation after being taught using CSR. The results showed that the use of CSR could enhance students’ reading comprehension achievement and participation in reading comprehension class. Hence, it is suggested for English teachers to use CSR in process of teaching and learning reading comprehension.